PERKEMBANGAN, PRODUKSI, DAN PERAN KULTUR MIKROALGA LAUT DALAM INDUSTRI - Diah Radini Noerdjito (OSEANA, 2019)
DEVELOPMENT, PRODUCTION, AND THE ROLE OF MARINE MICROALGA IN INDUSTRY. Microalgae cultures recently have been used for various purposes. Culture development of microalgae started from the late 1800s and still continue until now. Specific media composition, lighting, aeration, culture system were applied to many different species microalgae for specific purposes such as pharmaceutical, healthcare, cosmetics, environmental management, energy production, and aquaculture.